Effect of antacid on the bioavailability of cefprozil. - Shyu, W C (1992)
The effect of antacid on the bioavailability of cefprozil was investigated in a two-way crossover study. Eight healthy male subjects received a single 500-mg oral dose of cefprozil with and without coadministration of 30 ml of an antacid suspension containing magnesium hydroxide and aluminum hydroxide (Maalox). Cefprozil consists of cis and trans isomers in an approximate 90:10 ratio. When cefprozil was administered alone (treatment A), the mean maximum concentrations (Cmax) of the cis and trans isomers were 9.2 and 1.2 micrograms/ml, respectively. When cefprozil was coadministered with Maalox (treatment B), the Cmax values of the cis and trans isomers were 8.7 and 1.3 micrograms/ml, respectively. The mean values of the area under the curve from time zero to infinity (AUC0-infinity) were 27.7 and 3.5 micrograms.h/ml for treatment A and 27.5 and 3.5 micrograms.h/ml for treatment B for the cis and trans isomers, respectively. The other pharmacokinetic parameters, time to Cmax, elimination half-life, mean residence time, renal clearance, and percent urinary excretion, were essentially the same for the two isomers. The respective values of the elimination half-life for the cis and trans isomers were 1.36 and 1.32 h for treatment A and 1.36 and 1.42 h for treatment B. Mean urinary excretion was 63 and 60% for treatment A and 58 and 56% for treatment B for the cis and trans isomers, respectively. No significant differences between the two treatments were found for any of the pharmacokinetic parameters for either isomer. For the cis isomer, bioavailability point estimates (90% confidence intervals) of the mean Cmax and AUG0-infinity values for the Maalox treatment relative to those for the reference treatment were 95% (87%, 103%) and 99% (95%, 104%), respectively. For the trans isomer, the value were 109% (92%, 126%) for Cmax and 97% (88%, 106%) for AUC0-infinity. On the basis of the results of this study, it is concluded that the bioavailability of cefprozil is not affected by the coadministration of Maalox.